Identification of Factors Influencing Stunting in Children from Parent’s Perspective - Satriyono, Raden Danang Aryo Putro; Ramadani, Dinda Safitri (International Journal of Health Literacy and Science, 2024)
Stunting is a chronic under nutrition in early childhood and Indonesia still listed as one of the largest stunting percentage in the world with 21.6% in 2023. Indonesia has included stunting as one of their prioritize to tackle and encourage many health programs that aims to reduce it. Many of its program then focus on children but also their parents as parent playing an important role in this problem. But there is still very few research related to what factors influence the parents so their children can avoid stunting. This paper then analyse what factors affecting parents particular to stunting with variables related to perception and behaviour of human which is Extended theory of planned behaviour (TPB). Structural Equation Modelling (SEM) then was used to analyse all the variables correlation, The results of this study are that there are 4 significant correlations between variables, namely Descriptive Norm have a significant and negative effect on Intention to Use. This study also found that Attitude, Perceived Health Literacy and Perceived Economic Knowledge had a positive and significant effect. In addition, other findings are that Perceived Usefulness, Perceived Effectiveness and Perceived Behavioural Control do not have a significant effect on Intention to Use. This paper provide insight what factors that can be focused so stunting program so it can be more successful in the future.